PUPUK ORGANIK CAIR “JAKABA” SEBAGAI ALTERNATIF MEDIA PERTANIAN BERKELANJUTAN DI DESA BALONGDOWO - Isnaini Anniswati Rosyida; Yendra Erison; Natasya Isabel F; Sinta Wati; Izzatur Rohmah; Edi Susilo; Muh. Dandy Dwi P (Jurnal Pengabdian kepada Masyarakat, 2025)
Liquid Organic Fertilizer (POC), known as Jakaba (Eternal Lucky Mushroom), is an innovative natural fertilizer produced through a fungal fermentation process from various selected organic components. The main composition in making this fertilizer involves ingredients that are very easy to find in the surrounding environment, such as rice bran, shrimp paste (terasi), bean sprouts, rice washing water (leri), bamboo roots, bamboo leaves, and molasses as an energy source for microorganisms. The combination of these ingredients creates a nutrient-rich growing medium for Jakaba fungi, which then produces a fermented liquid with a very complete content of macro and micro nutrients for plants. Jakaba fertilizer has been widely known by farmers for its extraordinary ability to improve soil fertility and maintain overall plant health. For the people of Balongdowo Village, the application of this fertilizer is a strategic step and a sustainable choice in modern agricultural practices. This is because the production process is relatively easy, uses abundant natural ingredients, and is very friendly to environmental sustainability. The use of Jakaba provides a real solution for farmers to reduce dependence on synthetic chemical fertilizers, which if used excessively and continuously can damage the soil ecosystem, kill good microbes, and reduce land productivity in the long term.